2020
DOI: 10.1007/s10508-020-01696-w
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Disparities Mediating Increased Risky Sexual Behavior in Sexual Minorities: A Twin Approach

Abstract: Increased risky sexual behavior in sexual minorities relative to heterosexual individuals may be partly explained by mental health disparities, and both factors may be further jointly influenced by common genetic and environmental factors. However, these relationships have not been previously investigated. The objectives of the present study were to investigate mental health disparities as a mediator of the relationship between sexual orientation and risky sexual behavior, controlling for genetic and environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 64 publications
5
17
0
Order By: Relevance
“…Consistent with previous literature, nonheterosexuality was associated with increased risky sexual behavior indicated by lifetime sexual partners in the present study (Bränström & Pachankis, 2018;Charlton et al, 2011), psychosocial adversity (depressive and anxiety symptoms, early life adversities, and intimate partner violence) and substance use (King et al, 2008;Roberts et al, 2012;Rollè et al, 2018). Using a reduced factor structure, we replicated the finding from a previous study (Oginni et al, 2020) whereby mental health indicators partly mediated increased risky sexual behavior among sexual minority men and women. Our findings demonstrated that two mediation paths, through a separate substance use factor and in combination with increased psychosocial adversity, explained a larger proportion of the higher lifetime sexual partners among sexual minorities, especially women.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with previous literature, nonheterosexuality was associated with increased risky sexual behavior indicated by lifetime sexual partners in the present study (Bränström & Pachankis, 2018;Charlton et al, 2011), psychosocial adversity (depressive and anxiety symptoms, early life adversities, and intimate partner violence) and substance use (King et al, 2008;Roberts et al, 2012;Rollè et al, 2018). Using a reduced factor structure, we replicated the finding from a previous study (Oginni et al, 2020) whereby mental health indicators partly mediated increased risky sexual behavior among sexual minority men and women. Our findings demonstrated that two mediation paths, through a separate substance use factor and in combination with increased psychosocial adversity, explained a larger proportion of the higher lifetime sexual partners among sexual minorities, especially women.…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge, only one population-based study has investigated this possibility. Using a twin sample, mental health disparities were shown to mediate ten percent of the higher risky sexual behavior among sexual minorities (Oginni et al, 2020). By incorporating the genetic information from the sample (i.e., comparing similarities in identical and nonidentical twins), it was further shown that in contrast to previous findings indicating genetic correlations between sexual orientation, psychosocial factors, and risky sexual behavior including higher lifetime sexual partners (Ganna et al, 2019;Zietsch et al, 2010Zietsch et al, , 2012, this mediation relationship was not confounded by correlated (or overlapping) etiological genetic and individual-specific environmental influences.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the efforts to identify these factors that can explain elevated RSB rates in sexual minority people, few studies have investigated the disparities in correlates and predictors of RSB of sexual minority people compared to heterosexual people. Indeed, Oginni et al (2020) showed that mental health disparities mediated the impact of sexual orientation on RSB, and both externalizing disorders (e.g., alcohol and substance use) and internalizing disorders (e.g., depressive symptoms and anxiety) were higher in non-heterosexual individuals (King et al, 2008;Plöderl & Tremblay, 2015).…”
Section: Introductionmentioning
confidence: 99%